CABIN CREW TRAINING FUTURE AVIATION INDUSTRY TO THE PROFESSION IN TRAINING CENTERS UKRAINE - Радзівілова, І. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
This article deals about a research of a cabin crew member’s readiness problem for a professional activity at the aviational industry during the educational process in the Ukrainian training centers and the effect of dialogical methods and educationally-pedagogical interaction influence on an educational-disciplinary enrichment process